Does the Peruvian informal sector have a limit? Evidence of the effects of Venezuelan migration - Vera Rojas, Celia (2021)
The political, economic, social and humanitarian crisis that Venezuela is going through has driven the massive migration of Venezuelan citizens to Latin America. Peru is the second largest recipient of Venezuelan migrants in the region, hosting, as of July 2019, more than 850,000 citizens from this country1. Preliminary evidence suggests that the magnitude and speed of Venezuelan immigration would be influencing the functioning of the national labor market and the provision of public services, exposing the structural limitations of the Peruvian state institutions to facilitate the social and economic integration of the migrant population. in various areas of social life (Koechlin, Solórzano, Larco and Fernández-Maldonado, 2019; Valdiglesias, 2018).